2014
DOI: 10.1016/j.msea.2014.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Softening by severe plastic deformation and hardening by annealing of aluminum–zinc alloy: Significance of elemental and spinodal decompositions

Abstract: An Al-30 mol.% Zn supersaturated solid solution alloy was severely deformed using highpressure torsion (HPT) at 300 K and subsequently annealed at 373-673 K. The hardness and tensile strength significantly decreased and the tensile ductility increased with straining by HPT and reached a steady-state level at large imposed strains. Despite this softening behavior, the lattice strain was increased, Zn-rich particles were precipitated and the initial coarse grains were refined significantly to a size of ~190 nm w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 81 publications
2
21
0
Order By: Relevance
“…These superplastic behaviors, which occurred at 0.350.36T m , are considered as the first reports on achieving room-temperature superplasticity in any Mgand Al-based alloys. It should be noted that the application of ultra-SPD was essential to achieve room-temperature superplasticity as earlier attempts using the conventional SPD processing could not lead to room-temperatures superplasticity in the MgLi 7678) and AlZn 79,80) alloys. The MgLi and AlZn processed by ultra-SPD are not so stable at room temperature and they exhibit grain coarsening and unusual hardening during time due to the weakening of grain-boundary sliding.…”
Section: Room-temperature Superplasticitymentioning
confidence: 99%
“…These superplastic behaviors, which occurred at 0.350.36T m , are considered as the first reports on achieving room-temperature superplasticity in any Mgand Al-based alloys. It should be noted that the application of ultra-SPD was essential to achieve room-temperature superplasticity as earlier attempts using the conventional SPD processing could not lead to room-temperatures superplasticity in the MgLi 7678) and AlZn 79,80) alloys. The MgLi and AlZn processed by ultra-SPD are not so stable at room temperature and they exhibit grain coarsening and unusual hardening during time due to the weakening of grain-boundary sliding.…”
Section: Room-temperature Superplasticitymentioning
confidence: 99%
“…In the past two decades, numerous investigations were carried to study the microstructure and the mechanical properties of various SPD processed alloys, such as Al-Mg, Al-Zn-Mg, Cu-Zn, Cu-Al, Cu-Cr, Cu-Zr etc. [14][15][16][17][18][19][20][21][22][23]. However, no research was conducted to date to examine the effect of Mo solute atoms on the microstructure of UFG Ni processed by SPD, although Ni-Mo alloys have important practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…But under such conditions, the final microstructures are also difficult to control because of the strong interaction between defects and solute atoms. It has even been demonstrated that in some binary systems, namely Al–Cu and Al–Zn, the quenched supersaturated solid solutions are destabilized during SPD at room temperature (RT) leading to the nucleation and growth of a large density of precipitates. It has been proposed that the atomic mobility could be significantly enhanced during SPD especially thanks to the high vacancy concentration, solute drag by dislocations, pipe diffusion along dislocations, or grain boundary diffusion .…”
Section: Introductionmentioning
confidence: 99%